The Utilization of Differentiated Learning in Improving Physical Fitness and Active Lifestyle of Junior High School Students: Literature Review in Physical Education - Asep Akbaruddin; Mochamad Fajar Permana; Wahyu Saputra; Sumbara Hambali; Amat Komari; Wawan Sundawan Suherman (Pamukkale Spor Bilimleri Dergisi)
There are still very limited studies that integrate differentiated learning with physical education subjects that need to be studied more deeply, even though differentiated instruction is a learning model that adheres to the principles of Developmentally Appropriate Practice (DAP), where every learning experience must align with the characteristics and needs of students. This study aims to review the scientific literature in several countries regarding differentiated learning in physical education to improve physical fitness and active lifestyle. Article search is carried out with the help of the Harzing Publish or Perish program based on the Scopus database. The analysis of the search and screening of articles was carried out by the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) procedure. Of the 51 articles identified, only six remain in the criteria after the implementation of the exclusion stage. This research found that the application of differentiated learning (DL) in physical education (PE) to improve junior high school students' physical fitness and active lifestyle is still very limited and requires further research. In addition, in some literature, there is no previous research that specifically explores the impact of this model on junior high school students, so it is recommended for future researchers to add searches through various other databases, such as Web of Science, PubMed, and Google Scholar.